Workshop on Nature Restoration and Recovery (WKREST). ICES Scientific Reports - Adorf, Karolin; Andersone, Ingrida; Balestri, Elena; Banta, Gary; Blankett, Penina; Bos, Oscar; Bromhall, Katrina; Camilleri, Sarah; Canella, Cristina; Christensen, Helle Torp; Dickey Collas, Mark; Danovaro, Roberto; et al. (International Council for the Exploration of the Sea, 2025)
The Workshop on Nature Restoration and Recovery (WKREST) aimed to enhance understanding of restoration processes, success criteria, and the factors affecting recovery rates in line with international and national policy and legal frameworks. Participants reviewed available methods to model and measure the recovery rate and recovery times of marine habitats and species, and the ecosystem functions they provide (food webs, biodiversity, productivity and habitat provision) relevant to active and passive restoration initiatives. A wide range of ecosystem components, including fish, marine mammals, benthos, and birds, as well as the physical conditions that influence restoration outcomes, such as eutrophication, were examined, and the important role of connectivity in site selection and recovery were reviewed. WKREST noted that restoration timelines often exceed policy evaluation periods, creating challenges in demonstrating success. Furthermore, the importance of identifying baselines and target measure for success in restoration activities needs to be clearly formulated to be able to achieve success. Recovery rates vary widely among species and habitats, and monitoring programs must align with key habitat features and species life histories. Predictive modelling remains the most practical tool for assessing recovery at habitat and ecosystem scales, but mechanistic models are needed to capture dynamic environmental interactions and future changes, such as climate impacts and species interactions. Connectivity between local sites and the wider landscape is essential for successful restoration, and cooperation between neighbouring jurisdictions is critical, especially in transboundary areas. Significant knowledge gaps persist in understanding species dispersal and connectivity networks, particularly with respect to life-history traits. ICES can play a role in advancing marine restoration by enhancing knowledge on species recovery rates and ecological connectivity, particularly in offshore areas. Continued development of ICES databases and data visualization tools will improve ecosystem science and management advice. Strengthening international collaboration and integrating diverse datasets will be key to promoting effective and sustainable restoration practices.